Mobile Application-based Continuity of Care Training on Improving Midwifery Students' Knowledge - Wiwin Mintarsih Purnamasari; Yeni Fitrianingsih; Ari Indra Susanti; Lia Nurcahyani; Ida Sugiarti; Dini Mariani Dini Mariani; Herni Kurnia; Mardiana Ahmad (Sarana Ilmu Indonesia (Salnesia), 2025)
The quality of midwifery education is a key factor influencing maternal and newborn health outcomes and the achievement of global development goals. To address 21st-century challenges, midwives must be equipped with the skills provided by a competency-based Continuity of Care (CoC) curriculum aligned with educational standards. However, implementing CoC within learning methodologies and clinical guidance remains challenging. Technology-based training has emerged as an effective strategy to address these issues. This study aimed to analyze the effect of mobile CoC training on students’ knowledge. A pre-experimental one-group pretest-posttest design was conducted with 50 students selected through purposive sampling. Knowledge was measured using a validated structured questionnaire. Data analysis using the Wilcoxon test showed a significant increase in knowledge after the intervention (p-value <0,001). An effect size of 0,661 indicates that mobile application-based training has a strong influence (moderate-to-large category) on increasing students’ knowledge. The use of this application facilitated flexible, interactive access to materials, thereby enhancing students’ cognitive competence in providing continuous midwifery care.